2020
DOI: 10.1051/0004-6361/202038214
|View full text |Cite
|
Sign up to set email alerts
|

Chandra X-ray study confirms that the magnetic standard Ap star KQ Vel hosts a neutron star companion

Abstract: Context. KQ Vel is a peculiar A0p star with a strong surface magnetic field of about 7.5 kG. It has a slow rotational period of nearly 8 years. Bailey et al. (A&A, 575, A115) detected a binary companion of uncertain nature and suggested that it might be a neutron star or a black hole. Aims. We analyze X-ray data obtained by the Chandra telescope to ascertain information about the stellar magnetic field and/or interaction between the star and its companion. Methods. We confirm previous X-ray detections of K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Independent of the model details, we find a flux value of F X = 1.4 ± 0.1 × 10 −12 erg cm −2 s −1 in the 0.3−10.0 keV band. Overall, our analysis is in agreement, within the error bars, with the one presented by Oskinova et al (2020) from the same data, making an allowance for the solar abundances adopted by these authors.…”
Section: X-ray Emissionsupporting
confidence: 90%
See 1 more Smart Citation
“…Independent of the model details, we find a flux value of F X = 1.4 ± 0.1 × 10 −12 erg cm −2 s −1 in the 0.3−10.0 keV band. Overall, our analysis is in agreement, within the error bars, with the one presented by Oskinova et al (2020) from the same data, making an allowance for the solar abundances adopted by these authors.…”
Section: X-ray Emissionsupporting
confidence: 90%
“…HD 94660 has an effective temperature of T eff = 11 300 ± 400 K, a mass of 3.0 ± 0.2 M (Bailey et al 2015), and a rotation period of 2800 ± 200 d (Mathys 2017). A temperature of 11 300 K is indicative of a spectral type B8.5p (e.g., Eker et al 2020), rather than the A0p indicated by Renson & Manfroid (2009). Hensberge (1993) already reported long-term photometric variability with peak-to-peak amplitudes of ∼0.03 mag and determined a period on the order of 2700 d. Bailey et al (2015) estimated that HD 94660 has completed less than half of its main sequence lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality visual spectra of KQ Vel did not evidence any clear spectral signatures able to characterize the nature of the companion of the bright magnetic Ap star (Bailey et al 2015). On the other hand, KQ Vel is also a bright X-ray source whose origin cannot be simply related to the visible Ap star (Oskinova et al 2020). To explain how the X-ray emission from KQ Vel originates, different scenarios involving the unknown companion have been proposed.…”
Section: Summary On Kq Velmentioning
confidence: 99%
“…To explain how the X-ray emission from KQ Vel originates, different scenarios involving the unknown companion have been proposed. Oskinova et al (2020) considered various scenarios, including a possibility that the companion is a RS CVn-type binary consisting of late-type stars with high-level of coronal magnetic activity. This possibility was discarded because typical activity signs (e.g.…”
Section: Summary On Kq Velmentioning
confidence: 99%
See 1 more Smart Citation